2020
DOI: 10.1016/j.gaitpost.2020.08.088
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb movement characteristics of children and youth with dyskinetic cerebral palsy – A sensor approach

Abstract: Introduction:Children with dyskinetic cerebral palsy (DCP) suffer from involuntary movements, reflected in abnormal postures and jerky, fragmented movements (1). The severity of their motor abnormalities is currently evaluated with qualitative evaluation scales which are subjective and time-consuming. To objectify the deviating movement patterns of children with DCP, inertial sensors provide a userfriendly and cheap alternative. Inertial sensors have previously been successfully used to differentiate pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…These approaches require a welldefined movement pattern, and thus, prior work has focused mainly on lower extremity applications given the cyclical gait pattern. There has been limited use of SPM analyses to measure shoulder kinematics before this study [23][24][25][26][27] . While this SPM approach works well for comparing tightly controlled shoulder movements like in the current study, this may not always be the case with shoulder movements, given the vast workspace in which to move and generate force with the upper extremity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…These approaches require a welldefined movement pattern, and thus, prior work has focused mainly on lower extremity applications given the cyclical gait pattern. There has been limited use of SPM analyses to measure shoulder kinematics before this study [23][24][25][26][27] . While this SPM approach works well for comparing tightly controlled shoulder movements like in the current study, this may not always be the case with shoulder movements, given the vast workspace in which to move and generate force with the upper extremity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the population of Parkinson's disease and dyskinetic CP are not directly comparable, it indicates the potential of the proposed methodology for individuals with dyskinetic CP. A current study suggested that IMUs can be used as a mobile alternative for marker-based motion capture (omitting the need for an advanced movement laboratory) within upper extremity movements analysis of standardize movements in dyskinetic CP [14]. The proposed methodology goes one step further by using home-based collected IMUs data within unstandardized situations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the collection of data for 3D kinematics requires advanced motion capture systems, which do not allow outsidelab measurements. To enable measurements at home and in daily life environments, for CP, there is an increasing interest in using simpler systems for data collection, such as videobased markerless motion tracking (e.g., OpenPose) [12] and Inertial Measurements Units (IMUs) [13,14]. These easily applicable measurement systems, combined with machine learning models trained by algorithms (e.g., traditional such as logistic regression, random forest, support vector machine, or deep learning algorithms) may significantly contribute to the early detection of CP [15] and the monitoring of daily life functions [12,13].…”
Section: Introductionmentioning
confidence: 99%